(untitled) (Research, Society and Development, 2022)
Introduction: urinary tract infection (UTI) is one of the most frequent in the population, second only to those that affect the respiratory system. This pathology affects both sexes, with a prevalence in females. The main cause of UTIs is uropathogenic Escherichia coli (UPEC), representing up to 80% of infections. The patient’s symptoms may vary according to the anatomical site of the infection. The gold standard diagnosis of UTI is the uroculture with antibiogram, due to its possibility to identify the microorganism that is causing the infection and guide antibiotictherapy. As the treatment is usually made empirically, there is an increasement of bacterial resistance to the antibiotics used, making requiring studies to analyze the resistance profile of bacteria. Methodology: for the execution of this retrospective study, results for the year 2020 of positive urine cultures for E. coli with antibiogram from patients with community-acquired UTI were collected from a clinical analysis laboratory in Cascavel/PR. Results: 358 adequate results were obtained for the inclusion criteria. Of these, 84.63% were female. The age group most affected was from 0 to 4 years old, representing 22.90% of cases. Of the antibiotics studied, nalidixic acid, ampicillin with sulbactam, ampicillin, aztreonam, cephalothin, cefepime, ciprofloxacin, levofloxacin, norfloxacin and trimethoprim with sulbactam were above the 20% resistance threshold. The other evaluated drugs showed resistance below 20%, making their practice viable. Conclusion: E. coli presented different prevalences and incidences between this and other studies, making its constant monitoring important.